PLEYOTROPIC ANTIAGGREGANT EFFECTS OF AN INNOVATIVE ANTIARRHYTHMIC OF CLASS III SS-68, AN INDOLE DERIVATIVE - Saida Bogus; Aleksandr Dukhanin; Aida Kucheryavenko; Dmitry Vinakov; Konstantin Suzdalev; Pavel Galenko-Yaroshevsky (Belgorod National Research University, 2017)
Background: A new indole derivative with the lab code-number SS-68 demonstrates a significant antiarrhythmic (anti-fibrillation) activity associated with the predominant influence on potassium and calcium conductivity of cardiomyocytes plasmalemmas. The preliminary data give evidence of SS-68 possessing an antiaggregant activity. Methods: The influence of SS-68 on the platelet formation stage of hemostasis was determined by assessment of the anti-platelet effect (measuring platelet aggregation with Born/ O'Brien method), the dynamics of intracellular concentration of calcium ions in platelets was studied with FURA-2/АМ fluorescent probe. Results: Relative efficiency of the SS-68 indole derivative influence on platelet aggregation with the use of various inducers decreases in the following order: collagen > serotonin > ADP. The influence of SS-68 on platelet activity is characterized by pleiotropic effects: calcium-blocking effect, potentiation of cAMP-response, suppression of intracellular mechanisms of transmitting a stimulating signal, caused by the activation of collagen receptors. Conclusion: G-proteins are the most likely molecular targets of pleiotropic antiaggregant effect of SS-68. A more than threefold increase in the anti-platelet effect of SS-68 in vivo suggests the development of an active metabolite (metabolites).